(untitled) (Archive of Conferences, 2021)
Modern global climate warming has been proven by long-term meteorological observations, but the mechanisms and degree of its influence on natural ecosystems have not been sufficiently studied. The problem is so serious that it is being discussed at the UN, specialized scientific journals are being created, scientific projects of a planetary scale are being formed (Bartalev et al., 2008; Anenkhonov, 2012). The study of steppe territories is especially important in connection with the possibility of climatogenic aridization (Chen and Weber, 2014; Liu et al., 2014; Han et al., 2015).